Exploring Rural Healthcare Systems: An Administrative Learning Approach to Operations, Growth, and Success - May, Erin Rose (My University, 2025)
This report provides a comprehensive overview of my Applied Practice Experience (APE) at Clay County Medical Center (CCMC), a critical access hospital in Clay Center, Kansas, and my Integrated Learning Experience (ILE) completed at Kansas State University (KSU). The purpose of this experience was to apply and integrate public health knowledge, leadership, and administrative competencies in a real-world rural healthcare setting. The report begins with a review of literature on rural health disparities and social determinants of health, emphasizing the challenges that rural populations face. I completed more than 280 hours of supervised fieldwork. During this time, I accomplished several major projects including the revision of CCMC’s Strategic Plan and mission and vision statements, development of two new organizational policies (Personal Electronic Device Usage and Public Displays of Affection), creation of a standardized policy template, and design of two process maps illustrating the Policy Development Workflow and Billing Cycle. These efforts required the integration of competencies, not as isolated skills, but as interconnected tools. For example, revising the Strategic Plan required simultaneous application of leadership, systems thinking, policy development, collaboration with executive leadership, resource management, and evidence-based decision-making. Through these integrated experiences, I strengthened my ability to connect competencies and advance population health, while gaining a deeper understanding of the ethical, financial, and operational complexities of sustaining healthcare services inrural communities. My coursework in healthcare administration, epidemiology, environmental health, and behavioral public health provided a foundation for analyzing data, evaluating programs, and applying evidence-based decision-making to administrative practice. Collectively, these experiences demonstrate the integration of academic learning with applied public health practice and reinforce my commitment to advancing health equity, access, and quality outcomes in rural healthcare systems.
Keywords: rural healthcare systems; healthcare administration; healthcare operations; rural healthcare access barriers; health equity; systems-thinking and strategic planning